Influence of Spatial Attributes on Human Behavior in Complying with COVID-19 Health Protocols in The City Park of Puputan Badung Denpasar Bali - Ni Ketut Agusintadewi; Gede Wardana Putra; Widiastuti Widiastuti; Ni Putu Yunita Laura Vianthi (Pusat Kajian Bali Universitas Udayana, 2023)
The study aims to determine the most effective spatial setting for the fitness spots with pandemic mitigation in the city park of Puputan Badung Denpasar Bali as well as to identify various responses of human behavior in complying with health protocols. A mixed-method strategy was utilized, where a quantitative technique was used to determine the level of compliance. A qualitative inquiry with a case study method was also used to assess the influence of spatial attributes on human behavior. The respondents were selected using accidental sampling during peak times for a week. The sport activities observed were fitness, which was available in several spots of parks. Based on human behavior theories, the fitness space equipped with COVID-19 mitigation measures has not provided optimal stimuli to the people in complying with health protocols, leading to low compliance levels. The results of this study can be used as a reference to evaluate the effectiveness of implementing pandemic mitigation in the city park of Puputan Badung and other city parks with similar characteristics from an architectural perspective.